Case Report: Robot-assisted laparoscopic bladder diverticulectomy: a case series and initial experience - Ge, Guangju; Wang, Haihong; Zheng, Qiming; Zhang, Shuai; Wang, Huan; Ma, Liang (Frontiers in Surgery, 2025)
ObjectivesTo explore the experience of tumor control technique in robot-assisted laparoscopic bladder diverticulectomy (RALBD) in the treatment of bladder diverticulum tumor, intraoperative tumor control and postoperative comprehensive treatment.Patients and methodsWe treated three male patients with bladder diverticulum tumors. Case 1 involved a 63-year-old with a 3.0 cm tumor in the diverticulum on the right bladder wall. Case 2 involved a 70-year-old with a 1.0 cm cauliflower-like tumor in the diverticulum on the left bladder wall. Case 3 involved a 64-year-old with a 3.0 cm tumor in the diverticulum on the right bladder wall. Each patient underwent robot-assisted laparoscopic partial cystectomy (PC) with ureteral Double J (D-J) stent placement. To minimize the risk of intraoperative tumor spread, we implemented enhanced surgical techniques. Systemic chemotherapy and adjuvant intravesical chemotherapy were recommended to reduce the risk of tumor recurrence and metastasis.ResultsPostoperative pathology confirmed papillary urothelial carcinoma in all three cases. Each patient was followed up for over 20 months, with no evidence of recurrence or distant metastasis observed through cystoscopy and chest and abdominal CT scans.ConclusionFor patients with urothelial carcinoma in a bladder diverticulum, robot-assisted laparoscopic bladder-sparing surgery is a viable option when appropriate cases are selected. Effective intraoperative tumor control and comprehensive postoperative treatment are crucial to minimizing recurrence and metastasis risks. The robotic approach offers enhanced precision and visualization compared to traditional open or laparoscopic techniques, potentially leading to improved outcomes regarding intraoperative tumor control and reduced postoperative complications. However, this study is limited by its small sample size of only three patients and short-term follow-up. A larger sample of patients is needed to confirm the advantages of the robotic approach.